HISTORY TEACHING IN SCHOOLS OF UZBEKISTAN: PROBLEMS AND ACHIEVEMENTS - Avlokulova Gullola Xazratovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information on the subject of history, and emphasizes the teaching process of this subject in secondary schools. In addition, modern methods of studying history are also covered today.